Classification and properties of tuber- and root-based biocomposites - Jamal T.; Sapuan S.M.; Siddiqui V.U.; Syamsir A. (Elsevier, 2025)
An investigation into the characteristics and classification of biocomposites based on tubers and roots is presented in this chapter. The research explores the classification and inherent characteristics of materials derived from tubers and roots, providing information on their structural, mechanical, and thermal properties. An in-depth review of the properties and the manufacturing process of these biocomposites provides the foundation for understanding their possible applications. The findings of this study offer valuable perspectives for the comprehension of the distinctive characteristics of tuber- and root-based biocomposites. Additionally, it provides potential for future developments in materials science and engineering, notably in the area of sustainable and environment-friendly material innovations. ? 2025 Elsevier Ltd. All rights reserved.